CARDIOVASCULAR TOXICITY OF ANABOLIC-ANDROGENIC STEROIDS IN RECREATIONAL ATHLETES: MECHANISMS, CLINICAL PHENOTYPES, AND A PRACTICAL DIAGNOSTIC APPROACH - Mateusz Józef Gołdyn,; Jakub Michał Lichoń,; Marta Kras,; Agata Karasiewicz,; Maja Kuklo,; Dominik Łepecki,; Aleksandra Karolak,; Eliza Jakubowska, (International Journal of Innovative Technologies in Social Science, 2026)
Non-medical use of anabolic-androgenic steroids (AAS) has expanded beyond elite sports and is common among recreational strength trainees. Chronic supraphysiologic exposure is associated with adverse cardiovascular (CV) remodeling, accelerated atherosclerosis, and excess mortality. This review synthesizes evidence on AAS-associated CV toxicity and proposes a pragmatic diagnostic approach. Current data describe distinct clinical features in users: (i) often reversible cardiometabolic disturbances (dyslipidaemia, hypertension), (ii) structural remodeling, notably concentric left ventricular hypertrophy, (iii) impaired global longitudinal strain that can persist years after cessation, and (iv) premature coronary plaque burden linked to cumulative lifetime exposure. Furthermore, cardiac PET/CT studies indicate persistent coronary microvascular dysfunction, while registry cohorts confirm increased CV disease rates. Consequently, AAS use should be considered a major, under-recognized CV risk factor. We propose a phenotype-based assessment integrating non-judgmental history-taking, athlete-specific ECG interpretation, echocardiography with strain, and selective use of CMR and CCTA. Management should prioritize cessation support, harm reduction, and guideline-directed therapy tailored to the specific clinical phenotype (e.g., cardiomyopathy or coronary disease).